Peningkatan Kemampuan Menulis Teks Eksposisi Menggunakan Strategi Pembelajaran RAFT (Role, Audience, Format, Topic) Siswa Kelas VII SMP Negeri 3 Turatea Kabupaten Jeneponto - Anin Asnidar; M. Agus; Lulu Putri (Departement of Mathematics Education, 2023)
This study aims to improve the ability of class VII students of SMP Negeri 3 Turatea in learning to write text expositions using the RAFT learning strategy for the 2022-2023 academic year, with a total of 18 students. Data collection is done by testing techniques. The data obtained were analyzed using descriptive methods by classifying very high scores, high scores, moderate scores and low scores.This type of research is classroom action research which consists of cycle II, namely cycle I with 3 meetings and cycle II with 3 meetings. Researchers only focused on 1 class with a total of 18 students. The learning achievement of writing expository texts in the first cycle was 57.5 and the learning achievement in the second cycle was 60.5 and the learning achievement in the second cycle was 82.2. In cycle I, the category that was completed was 6 students with an achievement of 9.38%, the category that was not completed was 12 students with a percentage of 90.62%, the category that was not completed was 6 students with a percentage of 9.38%, which means an increase of 83.65%. Based on the results of the research above, it can be interpreted that the learning outcomes of writing exposition texts for class VII students of SMPN 3 Turatea can be increased by using the RAFT learning strategy (Role, Audience, Format, Topic).